Outcome of Continuous Low Dose Antibiotic Treatment in Comparison With Periintervention Antibiotic Prophylaxsis in Double J Stenting - Ahmed, Maruf; Islam, Md Nazrul; Islam, Amirul; Alam, Md Jahangir; Rahman, Md Mostafizur; Alam, Md Nabid (Bangladesh Journal of Urology, 2020)
Objective: To determine the outcome of antibiotic treatment regime in patient with indwelling DJ stenting having a per-interventional antibiotic prophylaxis compared with those of a continuous low-dose antibiotic treatment. Methods: A hospital based prospective experimental study was conducted in the Department of Urology of Dhaka Medical College Hospital, Dhaka from July 2012 to June 2014, to evaluate the antibiotic treatment regime in patient with indwelling DJ stenting, the benefits and disadvantages of a peri-interventional antibiotic prophylaxis compared with those of a continuous low-dose antibiotic treatment by enrolling a total number of 60 subjects in the department of Urology, Dhaka Medical College, Dhaka. Among 60 subjects 30 subjects were Group A comprised of subjects treated with continuous low dose antibiotic and Group B with 30 subjects treated with peri-interventional antibiotic. The patients would undergo temporary D J stent placement due to upper tract urolilhiasis who meet the inclusion criteria and exclusion criteria. Informed written consent would be taken from all patients. Urine samples would be analysed conventional antibiotic susceptibility and resistance was determined. All analyses was conducted at department of Microbiology, Dhaka medical college hospital. All patients who received peri-interventional antibiotic prophylaxis with 1g ceftriaxon was given l.v. at anaesthesia induction to obtain a peak concentration at the time of highest risk during the procedure.According to the pathogens profile and susceptibility, the antimicrobial agent of choice for continuous low-dose treatment was Cefixim 200mg twice daily. All stents placements were performed under sterile conditions applying a retrograde technique or antregrade in PCNL and open procedure under spinal or general anaesthesia. Patients were prescribed ketorolac (10mg) or Tramadol (50mg), while none of the patient received alpha blocker agents or anti-cholinergic drugs. Evaluations for UTI were performed before stent insertion and consecutively after 1, 2 and 4 weeks and/or at stent withdrawal. Statistical analysis of the result was obtained by using window based computer software devised with statistical packages for social science (SPSS-20 IBM) (SPSS inc, Chicago, IL, USA). The result was presented in tables, figures, and diagrams. Statistical test was done by Chi square test and Z test for qualitative data and t test for quantitative data. A p-value <0.05 is considered as level of significance. Results: To evaluate the antibiotic treatment regime in patient with indwelling DJ stenting, the benefits and disadvantages of a peri-interventional antibiotic prophylaxis compared with those of a continuous low-dose antibiotic treatment, a total number of 60 subjects were enrolled in this present study in the department of Urology, Dhaka Medical College, Dhaka. Among 60 subjects 30 subjects were Group A comprised of subjects treated with continuous low dose antibiotic and Group B with 30 subjects treated with periinterventional antibiotic only. Outcome of these two treatment techniques were studied. For urinary tract infection rate the concept of a peri-interventional antibiotic prophylaxis during DJ stent implantation is known to be better antibiotic coverage and is therefore recommended by the European Association of Urology. However, there is a lack of evidence concerning the exact antibiotic strategy for the entire stent-indwelling time. In clinical routine, it is an applied practice among urologists to continue antibiotic treatment in a low-dose fashion, even after previous uncomplicated implantations. Conclusion: In case of indwelling DJ stenting, subjects with continuous low dose antibiotic regimen had significantly less proportion of UTI, dysuria and frequency of micturition than those with peri-interventional antibiotic. So, if haematuria, skin rash and GIT disturbance is carefully managed then continuous low dose antibiotic regimen is better treatment option than peri-interventional regimen for with indwelling DJ stenting in different cases. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.127-136